The Evaluation of the International Sportsman Special School Coaching Program - Heri Wahyudi; Hari Setijono; Edy Mintarto (Jan Długosz University in Częstochowa, 2020)
This research is aimed to evaluate the quality of the International Sportsman School in East Kalimantan. The evaluations are context, input, process, and product. The CIPP model developed by Sufflebeam is used as a method. The results revealed that the context reviewed from the background and purpose of the establishment has been following the need for coaching the young athletes. Input selection shows that the athlete distribution in 10 districts has not spread equally, yet. Moreover, the infrastructures need more intensive improvement and treatment. Process evaluation shows that the implementation of the academic process and achievement coaching has been following the existing criteria. Then, the product evaluation shows that the academic report is good enough. But, for certain sports, it needs additional improvement in the achievement of all aspects. Hence, it can be concluded that the success of nursery, coaching, training, and management of the International Sports School cannot be separated from the human resources and other supporting systems such as funding and infrastructure.